The value of returning a sample of the Martian atmosphere - Timothy D. Swindle; Andreas Pack; Susanne P. Schwenzer; Edward D. Young (Proceedings of the National Academy of Sciences, 2025)
The elemental and isotopic abundances of major species in the Martian atmosphere have been determined, but analyses often lack sufficient precision, and those of minor and trace species are frequently not well known. Many important questions about the evolution and current state of Mars require the kind of knowledge that can be gained from analysis of a returned sample of the Martian atmosphere. Key target species include the noble gases, nitrogen, and various species containing carbon, hydrogen, and oxygen, such as methane. More detailed analyses will no doubt provide measurements of other species that will allow insights of their own. These volatiles can constrain the origin of the Martian atmosphere, exchange of volatiles between the surface and interior, polar processes, and (in the case of methane) the possibility of extant biology on Mars.